2017
DOI: 10.15436/2377-0619.17.1539
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Evaluation of Nutraceutical Molecules in Wastes of Fruit and Vegetables

Abstract: Fruit and vegetables wastes not only have no commercial value, but also require expensive operations of removal and disposal, representing a significant cost for the manufacturers of plant products. However, this material may represent an important resource of commercially worth phyto-molecules endowed with various nutraceutical properties. In the present work, we have verified the possibility of using fruit and vegetable waste materials as a source of bioactive compounds. Several nutraceutical compounds of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…. ), carotenoids, saponins, tannins, alkaloids, sterols, steroids, triterpenes, peptides and carbohydrates properties (Moure et al, 2001;Llorach et al, 2002;Zhang et al, 2017), which, as largely demonstrated, possess several biological activities, including antioxidant, antibacterial, antifungal, antiviral, antimicrobial, antidiabetic, anticancer, antidiarrhoeal, antihypertensive, antimutagenic, anti-inflammatory, anticholesterol and protective properties of cardiocirculatory system (Balasundram et al, 2006;Santana-Méridas et al, 2012;Nguyen, 2017). Increasing the yield of the target compounds adopting the most appropriate food waste recovery strategies, the economic value gained from them could be maximized.…”
Section: Food Waste Recovery Improves Sustainability Of Food Systemmentioning
confidence: 99%
“…. ), carotenoids, saponins, tannins, alkaloids, sterols, steroids, triterpenes, peptides and carbohydrates properties (Moure et al, 2001;Llorach et al, 2002;Zhang et al, 2017), which, as largely demonstrated, possess several biological activities, including antioxidant, antibacterial, antifungal, antiviral, antimicrobial, antidiabetic, anticancer, antidiarrhoeal, antihypertensive, antimutagenic, anti-inflammatory, anticholesterol and protective properties of cardiocirculatory system (Balasundram et al, 2006;Santana-Méridas et al, 2012;Nguyen, 2017). Increasing the yield of the target compounds adopting the most appropriate food waste recovery strategies, the economic value gained from them could be maximized.…”
Section: Food Waste Recovery Improves Sustainability Of Food Systemmentioning
confidence: 99%